"Green synthesis" of Silver Nanoparticles with Antimicrobial Activity Using Biomass of Microalgae (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
The biotechnological potential of microalgae lies in their rich content of proteins, vitamins, carotenoids, minerals, and other valuable compounds. In addition, microalgae have emerged as promising candidates for the “green synthesis” of nanoparticles (NPs). The aim of this study is to synthesize AgNPs using the “green biomass” of microalgae Parachlorella kessleri MDC6524 and Spirulina (Arthrospira) platensis Pc-005, and to evaluate their antimicrobial activity against conditionally pathogenic bacteria (Staphylococcus aureus, Enterococcus hirae, Salmonella typhimurium, Pseudomonas aeruginosa), and fungi (Aspergillus flavus, Penicillium aurantioviolaceum, Trichoderma viride). The “green synthesis” of AgNPs was carried out under illumination using the microalgae biomass. The UV-Vis spectroscopy of AgNPs derived from Parachlorella and Spirulina showed prominent absorption peaks at 440 and 425 nm, respectively. TEM results revealed that these AgNPs exhibit a spherical morphology with nanoscale dimension: 46 nm for Parachlorella-mediated AgNPs and 30 nm for Spirulina-mediated AgNPs. XRD pattern suggests that the biogenic NPs are well crystallized and have a high purity. Microalgae-derived AgNPs exhibited a significant antibacterial effect at low concentration (5-10 μg/mL) against the tested bacteria. Furthermore, AgNPs demonstrated a more pronounced effect on Gram-negative bacteria. However, AgNPs showed antifungal effects only at higher concentrations (100-300 μg/mL) compared to their antibacterial activity. This disparity is likely due to differences in the structure and composition of bacterial and fungal cell walls. Thus, microalgae-derived AgNPs can have a potential as antimicrobial agents and hold significant promise for future applications.
Keywords: Microalgae; silver nanoparticles; “green synthesis”; antimicrobial potential